Role of microbiome-gut-brain axis in autism spectrum disorder - Chand, Jagdish; Patel, Neha; Khare, Pragyanshu (Elsevier, 2025)
Autism spectrum disorder (ASD) is a neurological disorder that affects an individual's communication, behavior, and social interaction. Promising treatments specifically targeting the underlying neurophysiology of ASD are currently being developed. In this chapter, we review the pathophysiology and current pharmacological treatment options, along with the detailed role of the gut-brain axis in the ASD phenotype. The review integrates recent findings on the gut microbiota and ASD, addressing potential therapeutic interventions to restore a healthy balance of gut microbiome composition that can improve autism-associated symptoms.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Autism spectrum disorder; Central nervous system; Gut-brain axis; Microbiota